Laporan Kasus: Pemanfaatan MRI pada Diagnosis Fraktur Kompresi Vertebra Akut Post-Trauma - Frecilia Afrida; Ricky Ramadhian (Medula, 2026)
Vertebral compression fracture (VCF) is a common spinal injury, particularly among the elderly population with underlying osteoporosis. This condition may lead to severe pain, functional limitation, spinal deformity, and increased morbidity and mortality if not accurately diagnosed and managed. A comprehensive clinical and radiological approach is essential to establish the diagnosis and to differentiate acute traumatic fractures from chronic or pathological vertebral fractures. Magnetic resonance imaging (MRI) plays a crucial role in the evaluation of vertebral compression fractures due to its superior ability to assess soft tissues, spinal cord involvement, and bone marrow edema, which is a key indicator of acute injury. This case report describes a 68-year-old male with a known history of osteoporosis who presented to the emergency department following a fall from a height. The patient complained of severe lumbar pain and limited mobility without neurological deficits. MRI examination revealed an acute vertebral compression fracture characterized by bone marrow edema, with no evidence of paraspinal soft tissue involvement or spinal cord compression. These findings confirmed the diagnosis of an acute post-traumatic VCF in an osteoporotic patient. This case highlights the pivotal role of MRI in determining fracture acuity, evaluating spinal stability, detecting potential complications, and guiding appropriate management strategies. The appropriate utilization of MRI may improve diagnostic accuracy, facilitate timely intervention, and ultimately enhance clinical outcomes in patients with vertebral compression fractures.